2007
DOI: 10.1002/hep.21495
|View full text |Cite
|
Sign up to set email alerts
|

Role of caspase‐8 in hepatocyte response to infection and injury in mice†

Abstract: Caspase-8 has been implicated in signaling for apoptotic cell death and for certain nonapoptotic functions. However, knowledge of actual physiological or pathophysiological processes to which this enzyme contributes is lacking. Using a mouse model and employing the conditional knockout approach to delete the caspase-8 gene specifically in the liver, we found that caspase-8 deficiency in hepatocytes facilitates infection of the liver by Listeria monocytogenes, attenuates the hepatocyte proliferation wave during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 46 publications
2
60
2
Order By: Relevance
“…The increase in the CASP8 active fragment may be more related to the non-apoptotic functions of the protease in the liver, such as cell proliferation and induction of inflammation (Ben Moshe et al 2007). Surprisingly, we did not detect a corresponding increase in CASP8 activity in the liver.…”
Section: Caspases Expression and Processing Of Stk3 In The Livercontrasting
confidence: 75%
“…The increase in the CASP8 active fragment may be more related to the non-apoptotic functions of the protease in the liver, such as cell proliferation and induction of inflammation (Ben Moshe et al 2007). Surprisingly, we did not detect a corresponding increase in CASP8 activity in the liver.…”
Section: Caspases Expression and Processing Of Stk3 In The Livercontrasting
confidence: 75%
“…We found, however, that epidermal deficiency of caspase-8 did have a pronounced effect on skin homeostasis in that it gave rise to a chronic inflammatory disease associated with a hyperproliferative state. In a previous study we found that caspase-8 deficiency in hepatocytes promotes chronic inflammation in the liver after partial hepatectomy (Ben Moshe et al, 2007, 2008). The present study shows that widespread inflammation also develops in mice that express an enzymatically inactive caspase-8 allele.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also reported an inflammasome-independent role for caspase-8 in inhibiting extensive inflammation in vivo. 72,73 Conditional deletion of caspase-8 in hepatocytes, augments Listeria infection in liver and chronic inflammation following hepatectomy. 73 Caspase-8 deficiency also protects against inflammation-related hepatocarcinogenesis, while inducing Although Ub-RIP1 can enhance the phosphorylation of IRF3, it is also cleaved by activated caspase-8.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%
“…72,73 Conditional deletion of caspase-8 in hepatocytes, augments Listeria infection in liver and chronic inflammation following hepatectomy. 73 Caspase-8 deficiency also protects against inflammation-related hepatocarcinogenesis, while inducing Although Ub-RIP1 can enhance the phosphorylation of IRF3, it is also cleaved by activated caspase-8. Cleaved RIP1 inhibits IRF3 and NFκB thereby reducing the type I interferon (IFN) and IL-1β-/IL-18-mediated inflammatory responses.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%